Neuropharmacological evaluation of hormones in mice and insilico analysis of melatonin and somatostatin receptors - A. Babu Vimalanathan, Aniket Kumar, H. Naman Hirenkumar Shah, Manoj G Tyagi, Vinita Ernest, A. Kanikkai Raja (Recent Research in Science and Technology, 2010)
Spatial learning and memory consolidation are important aspects of human cognition. The test for motor co-ordination in mice is to characterize the motor phenotype of animals and also in relation to human beings. It is among the most fundamental aspects of everyday life as each physiological process that must be performed in order to achieve movement. In this study, depressive effect and effect on learning and memory of the two hormones, melatonin and somatostatin on animals was evaluated using the loco-motor activity test, rotarod and rectangular maze. The effect of Melatonin and Octreotide acetate alone and in combination with each other were estimated in Swiss albino mice. Melatonin was administered dose dependently and time dependently. Octreotide acetate was administered dose dependently. We compared the combined effect of these hormones for motor co-ordination, loco-motor activity and for the memory and learning behavior of animals. As per the present study, we found significant changes in the motor co-ordination, learning, and memory and depressive effect in animals and there was potentiated depression and attenuated learning and memory when the hormones were used in combination. In-silco analysis was conducted using Patchdock software and molecular docking of the ligands to their respective receptors conducted.